2018
DOI: 10.18502/kls.v4i4.2318
|View full text |Cite
|
Sign up to set email alerts
|

Different Intakes of Energy and Protein in Stunted and Non-stunted Elementary School Children in Indonesia

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
1
5
0
2
Order By: Relevance
“…Namun, kekurangan protein akan meningkatkan kerentanan terhadap penyakit dan gangguan pertumbuhan pada anakanak. 24 Hasil penelitian yang lain menunjukkan bahwa anak yang berumur 6 -24 bulan yang mengkonsumsi telur berhubungan dengan panjang badan lebih panjang dibandingkan dengan yang tidak mengkonsumsi telur (79,2 ± Formula Prebiotik Berbasis Pangan Lokal... AcTion: Aceh Nutrition Journal, November 2020 137 0,2 vs. 78,7 ± 0,1 cm; p = 0,03). 25 Hal ini menunjukkan bahwa jumlah dan mutu protein yang dikonsumsi dapat mempengaruhi kadar insulin like growth faktor (IGF-1) yang merupakan mediator hormon pertumbuhan dan juga sebagai faktor matrik protein dan pertumbuhan tulang yang berperan penting dalam pembentukan tulang.…”
Section: Perubahan Rerata Z-skor Menurutunclassified
“…Namun, kekurangan protein akan meningkatkan kerentanan terhadap penyakit dan gangguan pertumbuhan pada anakanak. 24 Hasil penelitian yang lain menunjukkan bahwa anak yang berumur 6 -24 bulan yang mengkonsumsi telur berhubungan dengan panjang badan lebih panjang dibandingkan dengan yang tidak mengkonsumsi telur (79,2 ± Formula Prebiotik Berbasis Pangan Lokal... AcTion: Aceh Nutrition Journal, November 2020 137 0,2 vs. 78,7 ± 0,1 cm; p = 0,03). 25 Hal ini menunjukkan bahwa jumlah dan mutu protein yang dikonsumsi dapat mempengaruhi kadar insulin like growth faktor (IGF-1) yang merupakan mediator hormon pertumbuhan dan juga sebagai faktor matrik protein dan pertumbuhan tulang yang berperan penting dalam pembentukan tulang.…”
Section: Perubahan Rerata Z-skor Menurutunclassified
“…Higher dietary utilizable protein intake was found to be a signi cant factor affecting body weight and BMI. Several studies also stated that an increased dietary protein intake was associated with a greater height, weight and BMI [42][43]. Increased dietary intake of utilizable protein, calcium and vitamin D was found to signi cantly increase height.…”
Section: Resultsmentioning
confidence: 98%
“…Higher protein intake was a significant factor in reducing the risk of stunting during school age (6-9 years old and 10-12 years old). Low protein intake was a substantial risk factor for stunting in school-aged children [55]. Lee's study on dietary protein consumption patterns in countries in Southeast Asia with high rates of stunting indicated that the predominant staples in the Southeast Asian diet were rice and other cereals, low levels of usable protein, and lack of essential amino acids and micronutrients.…”
Section: Discussionmentioning
confidence: 99%